Involuntary Retirement and the Resolution of the Retirement-Consumption Puzzle: Evidence in Australia - Barrett, G; Brzozowski, M (My University, 2010)
A substantial body of international research has shown that household expenditure on food and non-durables signicantly decreases at the time of retirement a finding that is inconsistent with the standard life-cycle model of consumption if retirement is an anticipated event. This fall in expenditure has become known as the `retirement- consumption puzzle.' We analyze rich Australian panel data to assess the Australian evidence on the puzzle. We nd strong evidence of a fall in expenditures on groceries, food consumed at home and outside meals with retirement. The observed decline in expenditure is explained by a subset of households experiencing an unanticipated wealth shock, such as a major health event or long-term job loss, at the time of retirement. This nding is corroborated by an analysis of alternative measures of household well-being, including indicators of nancial hardship, and self-reported nancial and life satisfaction. For the majority of households retirement is anticipated and there is no decline in economic welfare at retirement. However, for an important minority, retirement is `involuntary' and these households experience a marked decline across all indicators of economic well-being.
Social and Economic Dimensions of an Aging Population Research Paper
Keywords: Finance; Finance -- Expenditure and constraints on expenditure; Income, wealth and finances; Finance; Expenditure and constraints on expenditure; Income, wealth and finance